Application of buoyancy-power generator for compressed air energy storage using a fluid–air displacement system. (December 2019) - Samadi-Boroujeni, Hossein; Altaee, Ali; Khabbaz, Hadi; Zhou, John
Highlights: Compressed air energy storage combined with buoyancy power generation system. The round-trip efficiency of the fluid–air displacement system was between 53% and 62%. Gap distance between cylinder and wall is the most influential design parameters. Air wasting from buckets showed lowest impact on the resulting round trip efficiency of the system. Abstract: This study proposes a gravity power generator based on the fluid–air displacement system using Compressed Air Energy Storage from renewable energy sources to increase the solar and wind power system penetration in the power network. A computer model was applied to estimate the performance of the fluid–air displacement system, taking into account the effects of key design and operating parameters. Analysis of the system was performed to calculate the net energy generation as the difference between the energy input and the energy output. Simulation results indicated that the round-trip efficiency of the fluid–air displacement system was between 47% and 60%, assuming 80% compressor efficiency. Results also showed that a system generating the maximum energy density should have a speed of cylinders movement of 0.65 m/s, a cylinder-wall distance of 0.25 × diameter of the cylinder and a gap distance between centers of two tandem cylinders is equal to 1.25. Furthermore, a sensitivity analysis conducted on the main parameters of the system identified that the gap ratio and the buckets moving speed were the highly sensitive parameters to the design and operation of the proposed system. This study also demonstrates the feasibility of using the fluid-displacement system in energy storage from renewable energy technologies.